Glass composition, glass powder, sealing material, glass paste, sealed package, and organic electroluminescence panel

By adjusting the increase in fluidity of the glass composition and adding specific ingredients, such as V2O5 and TeO2, the problem of bubbles prone to occur in the packaging process of the glass composition is solved, and excellent anti-foaming performance is achieved, adhesion defects are avoided, and the luminous performance of OLED equipment is improved.

JP2025062304APending Publication Date: 2025-04-14AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023171273
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing glass compositions are prone to air bubbles (air foam) during packaging, resulting in bonding defects. Especially in organic electroluminescent (OLED) equipment, humid air will further reduce the luminescent performance, so a glass composition with excellent anti-foaming properties is needed.

Method used

By adjusting the fluidity increase rate of the glass composition, ensure that the fluidity increase rate reaches 1.10%/°C or higher in the range of 50°C to 70°C above the softening point of the glass, and contains components such as ваннียม oxide (V2O5) and tellurium oxide (TeO2), as well as zinc oxide (ZnO), to improve the anti-foaming performance of the glass composition.

Benefits of technology

The generation of air bubbles is reduced or eliminated during the packaging process, and the anti-foaming performance of the glass composition is improved, thereby avoiding the occurrence of bonding defects, and improving the luminous performance and reliability of equipment such as OLEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062304000002
    Figure 2025062304000002
  • Figure 2025062304000003
    Figure 2025062304000003
  • Figure 2025062304000004
    Figure 2025062304000004
Patent Text Reader

Abstract

To provide a glass composition having superior resistance to foaming.SOLUTION: A glass composition is substantially free of alkali metals and lead, wherein the rate of increase in fluidity per 1°C in a temperature range from 50°C above the softening point of the glass composition to 70°C above the softening point of the glass composition is 1.10% / °C or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass composition. The present invention also relates to a glass powder, a sealing material, a sealed package, and an organic electroluminescence panel. [Background technology]

[0002] A flat panel display (FPD) using an organic electro-luminescence display (OLED) and a plasma display (Plasma Display) or the like generally has a structure in which light-emitting elements are disposed between a pair of sealed glass substrates. Moreover, a liquid crystal display (LCD) generally has a structure in which liquid crystal is filled between a pair of sealed glass substrates. Furthermore, photovoltaic power generation panels such as organic thin-film solar cells and dye-sensitized solar cells generally have a structure in which a photoelectric conversion element is disposed between a pair of sealed glass substrates.

[0003] The above-mentioned glass substrates are sealed, for example, by disposing glass powder between a pair of glass substrates, melting the disposed glass powder, and sealing the substrates with a material derived from the solidified glass powder. As the glass composition contained in the glass powder used for such sealing, various glass compositions have been studied. For example, Patent Document 1 discloses a glass composition containing V2O5, TeO2, ZnO, and Bi2O3. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-066647 Summary of the Invention [Problem to be solved by the invention]

[0005] When the glass composition is used for sealing as described above, it is required that bonding defects do not occur. In particular, in OLEDs and the like, the light-emitting performance is reduced by moisture in the air, so a highly reliable sealing material that is less likely to cause bonding defects is required.

[0006] The present inventors have studied the glass composition described in Patent Document 1 and have found that voids (air bubbles) may occur in the molten glass composition during sealing, which may result in poor bonding. Furthermore, even when the glass composition is used for purposes other than sealing, the occurrence of voids (air bubbles) can cause various problems. For this reason, the glass composition may be required to have excellent resistance to bubbling when melted (hereinafter simply referred to as "resistance to bubbling").

[0007] The present invention has been made in view of the above problems, and an object of the present invention is to provide a glass composition that is excellent in bubbling resistance. Another object of the present invention is to provide a glass powder, a sealing material, a glass paste, a sealing package, and an organic electroluminescence panel. [Means for solving the problem]

[0008] As a result of extensive investigations into the above problems, the present inventors have found that the desired effects can be obtained by adjusting the rate of increase in fluidity of a glass composition relative to an increase in temperature, and have arrived at the present invention.

[0009] That is, the inventors discovered that the above problems can be solved by the following configuration. [1] A glass composition that is substantially free of alkali metals and lead, A glass composition having a fluidity increase rate per degree Celsius of 1.10% / °C or more in a temperature range from 50°C higher than the softening point of the glass composition to 70°C higher than the softening point of the glass composition. [2] The glass composition according to [1], containing at least vanadium and tellurium. [3] In mole percent based on oxide, Contains 25.0-50.0% V2O5, 20.0-50.0% TeO2, and 5.0-30.0% ZnO; The glass composition according to [2], wherein the total content of V2O5, TeO2, and ZnO is 84.0 to 92.0%. [4] In mole percent based on oxide, Contains 0.1 to 5.0% of one or more selected from the group consisting of Al2O3, La2O3, Y2O3, and CuO; The glass composition according to [2] or [3], wherein the total content of V2O5 and TeO2 is 63.0 to 70.0%. [5] Further, the composition contains one or more components selected from the group consisting of phosphorus and copper, In mole percent based on oxide, Contains 42.0-52.0% TeO2. The glass composition according to any one of [2] to [4], wherein the total content of V2O5 and TeO2 is 70.0 to 85.0%. [6] In mole percent based on oxide, Contains 0.1 to 5.0% of one or more selected from the group consisting of La2O3 and Y2O3, The glass composition according to any one of [1] to [5], wherein the content of BaO is 0.1 to 4.5%. [7] The glass composition according to any one of [1] to [6], wherein the content of Nb2O5 is 2.0 to 10.0%, expressed in mole percent on an oxide basis. [8] A glass powder comprising the glass composition according to any one of [1] to [7], wherein the volume-based 50% particle size in a cumulative particle size distribution is 0.1 to 100 μm. [9] A sealing material comprising the glass powder according to [8] and at least one of a low expansion filler and an electromagnetic wave absorbing substance.

[10] A glass paste comprising the glass powder according to [8] and an organic vehicle.

[11] The glass paste according to

[10] , further comprising at least one of a low expansion filler and a laser absorbing substance.

[12] A first substrate; a second substrate disposed opposite the first substrate; a sealing layer disposed between the first substrate and the second substrate and bonding the first substrate and the second substrate together; A sealed package, wherein the sealing layer comprises the glass composition according to any one of [1] to [7].

[13] A liquid crystal display device comprising, in this order, a substrate, a laminated structure having an anode, an organic thin film layer, and a cathode, and a glass member; a sealing layer that bonds the substrate and the glass member; The sealing layer of an organic electroluminescence panel includes the glass composition according to any one of [1] to [7]. Effect of the Invention

[0010] According to the present invention, a glass composition having excellent bubbling resistance can be provided. The present invention also provides a glass powder, a sealing material, a glass paste, a sealing package, and an organic electroluminescence panel. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a plan view showing a state in which an electronic element is sealed in a sealed package. [Diagram 2] FIG. 2 is a cross-sectional view taken along line AA in FIG. [Diagram 3] 4 is a cross-sectional view showing a state in which a pre-fired layer is formed on one surface of a second substrate. FIG. [Figure 4] FIG. 2 is a cross-sectional view showing a state in which a first substrate and a second substrate are superimposed on each other. [Diagram 5] FIG. 4 is a cross-sectional view showing a state in which the provisionally fired layer is fired by irradiation with laser light to form a sealing layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The following description of the configuration may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment.

[0013] The meaning of each description in this specification is as follows. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0014] <Glass composition> The glass composition of the present invention is substantially free of alkali metals and lead, and has a fluidity increase rate per degree Celsius of 1.10% / °C or more in the temperature range from 50°C higher than the softening point of the glass composition to 70°C higher than the softening point of the glass composition. The glass composition of the present invention is characterized by having the above-mentioned fluidity increase rate. For example, when sealing is performed using the glass composition of the present invention, the temperature of the glass composition is increased, and bubbles may be generated in the glass composition. Here, since the glass composition of the present invention has the above-mentioned fluidity increase rate, when bubbles are generated by increasing the temperature of the glass composition, the bubbles are easily released from the glass composition, and it is considered that anti-foaming is obtained as a result.

[0015] [composition] A preferred composition of the glass composition of the present invention will now be described. Substantially free of alkali metals means that no alkali metals are contained other than unavoidable impurities, that is, no alkali metals are intentionally added. In the glass composition of the present invention, the content of alkali metals, expressed as the total amount of alkali metal oxides, is preferably 1000 ppm by mass or less, and more preferably 500 ppm by mass or less, based on the total mass of the glass composition. In this specification, alkali metal means Li (lithium), Na (sodium) and K (potassium), and alkali metal oxide means Li2O, Na2O and K2O.

[0016] Furthermore, "substantially free of lead" means that it contains no lead other than unavoidable impurities, that is, it means that lead is not intentionally added. In the glass composition of the present invention, the content of lead, calculated as lead oxide (PbO), is preferably 1000 ppm by mass or less, and more preferably 500 ppm by mass or less, based on the total mass of the glass composition.

[0017] The glass composition of the present invention is not particularly limited as long as it does not contain alkali metals or lead and has the above-mentioned fluidity increasing rate. However, in order to lower the glass transition temperature (hereinafter also referred to as "Tg") of the glass composition, it is preferable to contain at least vanadium (V) and tellurium (Te). Vanadium and tellurium are preferably contained in the glass composition as their respective oxides, and it is preferable to contain at least V2O5 and TeO2. The content of V2O5 is preferably 25.0% or more in mole percent based on the oxides, and the content of TeO2 is preferably 20.0% or more in mole percent based on the oxides.

[0018] In the following description of the content of each oxide component in the glass composition of the present invention, unless otherwise specified, it is expressed as mol % based on the oxide with respect to the entire glass composition. In this specification, the content of each oxide component is measured by X-ray fluorescence analysis.

[0019] The glass composition of the present invention preferably contains a component other than V2O5 and TeO2. Examples of the component other than V2O5 and TeO2 include ZnO, Ag2O, BaO, and B2O3, with ZnO being preferred. That is, the glass composition of the present invention preferably contains V2O5, TeO2 and ZnO.

[0020] When the glass composition of the present invention contains V2O5, TeO2 and ZnO, the total content of these components is preferably 84.0 to 92.0%. In addition, when the above total content is satisfied, the content of V2O5 is preferably 25.0% or more, and more preferably 35.0% or more, in order to lower Tg, and is preferably 50.0% or less, and more preferably 45.0% or less, in order to provide a glass composition with excellent water resistance. When the above total content is satisfied, the content of TeO2 is preferably 20.0% or more, more preferably 22.0% or more, in order to lower the Tg, and is preferably 50.0% or less, more preferably 35.0% or less, in order to reduce the thermal expansion coefficient. When the above total content is satisfied, the ZnO content is preferably 5.0% or more, more preferably 15.0% or more, in order to reduce the thermal expansion coefficient, and is preferably 32.0% or less, more preferably 30.0% or less, in order to suppress moisture permeation.

[0021] In the composition having the above-mentioned preferred contents, it is also preferable to further contain one or more components selected from the group consisting of Al2O3, La2O3, Y2O3, and CuO, in order to provide a glass composition with better water resistance. The content of each of the above components is preferably 0.1 to 5.0%. The total content of the above additional components is preferably 1.0% or more, and more preferably 2.0% or more, in order to provide a glass composition with better water resistance. The total content of the above additional components is preferably 4.5% or less, and more preferably 4.0% or less, in order to lower Tg. In the embodiment containing the above additional components, the total content of V2O5 and TeO2 is preferably 63.0% or more in order to increase the fluidity increase rate, and the total content of V2O5 and TeO2 is preferably 70.0% or less in order to improve water resistance.

[0022] When the glass composition of the present invention contains V2O5, TeO2 and ZnO, the total content of the above components is also preferably 83.0 to 89.0%. In addition, when the above total content is satisfied, the content of V2O5 is preferably 20.0% or more, and more preferably 25.0% or more, in order to lower Tg, and is preferably 40.0% or less, and more preferably 35.0% or less, in order to provide a glass composition with excellent water resistance. When the above total content is satisfied, the content of TeO2 is preferably 30.0% or more, more preferably 42.0% or more, in order to lower the Tg, and is preferably 60.0% or less, more preferably 52.0% or less, in order to reduce the thermal expansion coefficient. When the above total content is satisfied, the ZnO content is preferably 5.0% or more, more preferably 6.0% or more, in order to reduce the thermal expansion coefficient, and is preferably 15.0% or less, more preferably 10.0% or less, in order to suppress the occurrence of loss of transparency. In the composition with the above preferred contents, it is also preferable to further contain one or more components selected from the group consisting of phosphorus (P) and copper (Cu) as components for stabilizing the glass, and more preferably to contain one or more components selected from the group consisting of P2O5 and CuO. The content of each of the above components is preferably 0.1 to 5.0%. The total content of the above additional components is preferably 1.0% or more, and more preferably 2.0% or more, in terms of providing a glass composition with a better water resistance. The total content of the above additional components is preferably 10.0% or less, and more preferably 7.0% or less, in terms of lowering Tg. In the embodiment containing the above additional components, the total content of V2O5 and TeO2 is preferably 70.0% or more, more preferably 75.0% or more, from the viewpoint of increasing the fluidity increase rate, and the total content of V2O5 and TeO2 is preferably 85.0% or less, more preferably 80.0% or less, from the viewpoint of water resistance.

[0023] The glass composition of the present invention preferably contains a Group 2 element component. More specifically, it preferably contains one or more components selected from the group consisting of MgO, CaO, SrO and BaO, more preferably contains one or more components selected from the group consisting of CaO and BaO, and further preferably contains BaO. When the glass composition of the present invention contains Group 2 element components, the total content thereof is preferably 0.1% or more, more preferably 0.3% or more, in order to further enhance the stability of the glass composition. The total content of Group 2 element components is preferably 4.5% or less, more preferably 3.0% or less, and even more preferably 2.5% or less, in order to make the glass composition less likely to crystallize. In particular, the content of BaO is preferably within the above-mentioned preferred range. The content of BaO may be 0.0%.

[0024] The glass composition of the present invention preferably contains Nb2O5. When the glass composition of the present invention contains Nb2O5, the content is preferably 2.0% or more, more preferably 4.0% or more, in order to reduce the thermal expansion coefficient. The content of Nb2O5 is preferably 10.0% or less, more preferably 8.0% or less, in order to lower Tg.

[0025] The glass composition of the present invention may contain B2O3. When the glass composition of the present invention contains B2O3, the content is preferably 0.5% or more, more preferably 0.7% or more, in order to further increase the stability of the glass composition. The content of B2O3 is preferably 10.0% or less, more preferably 7.0% or less, and even more preferably 5.0% or less, in order to make the glass composition less likely to crystallize.

[0026] The glass composition of the present invention may contain Bi2O3. When the glass composition of the present invention contains Bi2O3, the content is preferably 0.3% or more, more preferably 0.5% or more, from the viewpoint of increasing the adhesive strength. The content of Bi2O3 is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 3.5% or less, from the viewpoint of lowering Tg.

[0027] In addition, since the above-mentioned CuO can absorb light, when the glass composition of the present invention contains CuO, the glass composition of the present invention can be heated, for example, by electromagnetic waves such as light (preferably laser light). In addition, Fe2O3 and MnO can also be mentioned as light absorbing components, and can impart light absorbing ability to the glass composition of the present invention. Therefore, the glass composition of the present invention preferably contains one or more components selected from the group consisting of CuO, Fe2O3 and MnO. Of these, it is preferable that the glass composition contains CuO.

[0028] The glass composition of the present invention may contain components other than the above components (hereinafter also referred to as "other components") within a range that does not impair the object of the present invention. The total content of other components is preferably 10.0% or less. Other components include, for example, CeO2, TiO2, ZrO2, MoO3, WO3, CoO, GeO2, and Sb2O3.

[0029] [Characteristics] The characteristics of the glass composition of the present invention will now be described.

[0030] The glass composition of the present invention has a fluidity increase rate per degree Celsius of 1.10% / ° C. or more in the temperature range from 50° C. higher than the softening point of the glass composition to 70° C. higher than the softening point of the glass composition. The liquidity increase rate will be explained below.

[0031] The softening point (Ts) of the glass composition is measured using a differential thermal analysis (DTA) device. Specifically, the glass composition is powdered, DTA is performed on the powder, and the DTA curve is analyzed to calculate Ts (unit: °C). In the differential curve of the DTA curve, a first endothermic peak corresponding to the glass transition point, a second endothermic peak corresponding to the glass softening temperature, and a first exothermic peak corresponding to the crystallization temperature are observed. At this time, the temperature of the fourth inflection point in the DTA curve is defined as Ts. For detailed measurement methods, refer to the methods described in the Examples.

[0032] The liquidity increase rate is calculated in the following manner. First, the value of Ts (unit: °C) obtained by the above method is rounded off to obtain a value (T1). The temperature 50°C higher than T1 is defined as T50 (unit: °C), and the temperature 70°C higher than T1 is defined as T70 (unit: °C). Next, the powder of the glass composition is formed into a cylindrical molded body having a diameter of 15 mm. The molded body is obtained by filling the glass composition having a specific gravity g into a cylindrical press mold having an inner diameter of 15 mm and press-molding the glass composition at a pressure of 10 to 100 kgf. The molded body is held at the above temperatures T50 and T70 to obtain a sintered molded body. That is, a sintered molded body sintered at T50 and a sintered molded body sintered at T70 are obtained. The holding time at the above temperatures is 10 minutes, and the temperature is raised from room temperature to the above temperatures at a rate of 10°C / min. The diameter of the obtained fired molded body is measured. The diameter is measured in four directions at 45° intervals, and the average value of the diameters is used as the diameter of the fired molded body. From the above measurements, the fluidity increase rate is calculated using the following formula (1). In the following formula (1), fd represents the fluidity increase rate (unit: % / °C). R50 represents the diameter (unit: mm) of the sintered molded body sintered at T50, and R70 represents the diameter (unit: mm) of the sintered molded body sintered at T70. T50 and T70 are as described above. In addition, in formula (1), D represents the diameter (unit: mm) of the molded body and is 15 mm. (1) fd = (R70-R50) / {(T70-T50)×D}

[0033] That is, the fluidity increase rate (fd in formula (1)) represents the degree of improvement in fluidity when changing from T50 to T70, and it can be said that the larger this value is, the easier the fluidity is to be improved by increasing the temperature. Therefore, as described above, it is considered that the glass composition of the present invention has excellent bubble resistance. In the glass composition of the present invention, the fluidity increase rate is 1.10% / ° C. or more, preferably 1.15% / ° C. or more, and more preferably 1.30% / ° C. or more. There is no particular upper limit to the fluidity increase rate, but it may be, for example, 3.00% / ° C. or less, and preferably 2.00% / ° C. or less.

[0034] The glass transition point of the glass composition of the present invention is preferably 310° C. or lower, more preferably 300° C. or lower, and even more preferably 290° C. or lower, in terms of better resistance to foaming. The lower limit of the glass transition point is not particularly limited, but is often 200° C. or higher, and preferably 250° C. or higher. The glass transition point (Tg) can be calculated from the above DTA curve, and the temperature at the intersection of the first inflection point and the second inflection point of the DTA curve (the peak in the differential curve of the DTA curve) is taken as Tg (unit: ° C.).

[0035] The glass composition of the present invention preferably has excellent water resistance. The water resistance refers to a state in which the weight loss of the glass composition of the present invention is small when the glass composition is brought into contact with water. Specifically, the water resistance is evaluated by the following procedure. First, a cylindrical glass block (diameter 5 mm, height 20 mm) selected from the group consisting of the glass compositions of the present invention is used as a sample. The sample is placed in a container filled with distilled water, and the container is kept at 85°C and left for 24 hours. The mass of the sample after 24 hours is compared with the mass of the sample before immersion in distilled water to calculate the mass reduction rate (ΔW). The mass reduction rate is expressed by the following formula (2). In formula (2), Wb represents the mass of the sample before immersion in distilled water, and Wa represents the mass of the sample after 24 hours of immersion in pure water. Equation (2) ΔW = 100 × (Wb-Wa) / Wb The value of ΔW is preferably less than 0.8%.

[0036] [Manufacturing method] The method for producing the glass composition of the present invention can be, for example, the method shown below. Note that the method for producing the glass composition of the present invention is not limited to the method shown below as long as the above-mentioned glass composition of the present invention can be obtained.

[0037] First, a mixture of raw materials is prepared. The raw materials may be those used in the manufacture of ordinary oxide-based glasses. Specifically, oxides and carbonates of the above elements may be used. The raw material mixture is obtained by mixing raw materials while adjusting the ratio and type of the raw materials so as to obtain a desired glass composition.

[0038] Next, the obtained raw material mixture is heated by a known method to obtain a melt. The temperature at which it is heated to melt (melting temperature) is preferably 950° C. or higher, and more preferably 1000° C. or higher. The melting temperature is preferably 1200° C. or lower, and more preferably 1150° C. or lower. The time for heating and melting is not particularly limited, but may be, for example, 30 to 90 minutes.

[0039] The resulting molten material is cooled and solidified to obtain the glass composition of the present invention. The cooling method is not particularly limited, and a roll-out machine, a press machine, or the like may be used, or the glass composition may be rapidly cooled by dropping it into a cooling liquid. The obtained glass composition preferably has a crystallinity of 0%, i.e., is amorphous. However, it may contain crystallized portions as long as the effects of the present invention are not impaired.

[0040] The form of the glass composition of the present invention is not particularly limited, and may be adjusted depending on the purpose of use. Examples of the form of the glass composition of the present invention include a block form, a plate form, a flake form, and a powder form. From the viewpoint of using the glass composition of the present invention as a sealing material, it is preferably in a powder form.

[0041] <Glass powder> The glass powder of the present invention comprises the above-mentioned glass composition of the present invention. The glass powder selected from the group consisting of the glass compositions of the present invention means that the average composition of the glass powder is the same as that of the glass composition of the present invention. That is, the glass powder of the present invention may be composed of a single glass powder having the same composition as that of the glass composition of the present invention. The glass powder of the present invention may also be a glass powder obtained by mixing two or more glass powders having different compositions so that the average composition is the same as that of the glass composition of the present invention. Hereinafter, for convenience, the glass powder of the present invention, which is composed of two or more glass powders having different compositions, is also referred to as a "glass powder mixture."

[0042] The particle size of the glass powder of the present invention can be appropriately selected depending on the application. From the viewpoint of use as a sealing material, the glass powder of the present invention preferably has a 50% particle size on a volume basis in a cumulative particle size distribution of 0.1 to 100 μm. Furthermore, when the glass powder of the present invention is used as a glass paste described below, the 50% particle size on a volume basis in the cumulative particle size distribution is preferably 0.1 to 5 μm, and more preferably 0.1 to 2.5 μm.

[0043] In this specification, the 50% particle size on a volume basis in the cumulative particle size distribution is determined from a particle size distribution measured using a laser diffraction / scattering particle size distribution measuring device. The 50% particle size on a volume basis in the cumulative particle size distribution is D 50 It is also said.

[0044] The glass powder can be obtained by a known method, for example, by pulverizing the glass powder of the present invention. The pulverization method can be performed by using known means, such as a jaw crusher, a roll crusher, an attritor, a vibration ball mill, a rotary ball mill, a planetary ball mill, a jet mill, and a media stirring mill (bead mill). Glass powder D 50 can be adjusted by the above-mentioned grinding method and grinding conditions. 50In the case where the particle size is to be 5 μm or less, for example, a wet mill is preferably used. In the wet milling, for example, in the above-mentioned various ball mills, a medium such as alumina, zirconia, or yttria-stabilized zirconia, a glass composition, and a medium (for example, water, alcohol) are placed in a milling container and milled. The glass powder obtained by pulverization may be classified by a known method, such as a sieve, a dry cyclone, or a wet cyclone.

[0045] When obtaining a glass powder mixture, the compositions of the two or more glass powders having different compositions are not particularly limited, and the average composition may be adjusted to be the same as that of the glass composition of the present invention. For example, the glass powder mixture may be composed of two glass powders having different compositions, or may be composed of three glass powders having different compositions.

[0046] The glass powder of the present invention can be preferably used as a sealing material. When the glass powder of the present invention is used as a sealing material, it has excellent foaming resistance and is less likely to cause poor bonding. The method of using the glass powder of the present invention as a sealing material and the sealing method will be described in detail later.

[0047] <Sealing material> The sealing material of the present invention contains the glass powder of the present invention. The sealing material of the present invention preferably contains the glass powder and at least one of a low expansion filler and an electromagnetic wave absorbing substance. The sealing material of the present invention may contain both a low expansion filler and an electromagnetic wave absorbing material.

[0048] When the sealing material contains a low expansion filler, the thermal expansion coefficient of the sealing layer formed using the sealing material can be adjusted. The low expansion filler is preferably at least one selected from the group consisting of silica, alumina, zirconia, zirconium silicate, cordierite, zirconium phosphate compounds, soda lime glass, and borosilicate glass. The zirconium phosphate compounds include (ZrO)2P2O7, NaZr2(PO4)3, KZr2(PO4)3, Ca0.5 Examples include Zr2(PO4)3, NbZr(PO4)3, and Zr2(WO3)(PO4)2, as well as complex compounds thereof. Low expansion filler D 50 The thickness is preferably 0.1 to 5.0 μm, and more preferably 0.1 to 2.0 μm.

[0049] The content of the low-expansion filler can be appropriately adjusted depending on the desired thermal expansion coefficient of the sealing layer. The content of the low-expansion filler is preferably 1% or more, more preferably 5% or more, and more preferably 10% or more, based on the total volume of the sealing material. From the viewpoint of the fluidity of the sealing material during sealing, the content of the low-expansion filler is preferably 50% or less, more preferably 45% or less, and even more preferably 40% or less, based on the total volume of the sealing material.

[0050] In addition, when the sealing material contains an electromagnetic wave absorbing substance, the sealing material can be selectively heated by electromagnetic waves. The electromagnetic waves are not particularly limited, and examples thereof include microwaves, infrared rays, visible light, and ultraviolet rays, with infrared rays, visible light, and ultraviolet rays being preferred, and infrared rays or visible light being more preferred. That is, the electromagnetic wave absorbing substance is preferably a light absorbing substance. In this specification, infrared rays refer to electromagnetic waves having a wavelength longer than 760 nm and shorter than 1 mm. In addition, in this specification, visible light refers to electromagnetic waves with a wavelength longer than 360 nm and shorter than 760 nm. In addition, in this specification, ultraviolet light refers to electromagnetic waves having a wavelength longer than 200 nm and shorter than or equal to 360 nm. Examples of electromagnetic wave absorbing substances (light absorbing substances) include one or more metals selected from the group consisting of Cr, Mn, Fe, Ni, Co, and Cu, or metal oxides containing one or more metals selected from the above group. The electromagnetic wave absorbing material may be any material other than those exemplified above as long as it absorbs electromagnetic waves. For example, known inorganic pigments are preferred. In addition, the light absorbing material can be appropriately selected depending on the wavelength of the light irradiated during sealing. Electromagnetic wave absorbing material D 50The thickness is preferably 0.1 to 5.0 μm, and more preferably 0.1 to 2.5 μm.

[0051] The content of the electromagnetic wave absorbing substance is preferably 0.1% or more, more preferably 1% or more, and even more preferably 2% or more, based on the total volume of the sealing material in terms of facilitating heating of the sealing material, and is preferably 20% or less, more preferably 15% or less, and even more preferably 12% or less, based on the total volume of the sealing material in terms of the fluidity of the sealing material during sealing. When the glass composition of the present invention contains the above-mentioned light absorbing component, the total amount of the light absorbing component and the electromagnetic wave absorbing substance is preferably within the above-mentioned range.

[0052] <Glass paste> The glass paste of the present invention contains the above-mentioned glass powder of the present invention and an organic vehicle. The glass paste of the present invention may contain a component contained in the sealing material. Hereinafter, a mixture of the glass powder contained in the glass paste of the present invention and a component that the sealing material may contain is also referred to as a "mixed material." Even if the glass paste of the present invention contains only glass powder, the glass powder is conveniently referred to as the mixed material.

[0053] As the organic vehicle, for example, a solvent in which a resin, which is a binder component, is dissolved, is used. Specifically, a resin such as methyl cellulose, ethyl cellulose, carboxymethyl cellulose, oxyethyl cellulose, benzyl cellulose, propyl cellulose, or nitrocellulose dissolved in a solvent such as terpineol, texanol, butyl carbitol acetate, or ethyl carbitol acetate can be used as the organic vehicle. Also, an acrylic resin such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, or 2-hydroxyethyl (meth)acrylate dissolved in a solvent such as methyl ethyl ketone, terpineol, texanol, butyl carbitol acetate, or ethyl carbitol acetate can be used as the organic vehicle. In this specification, (meth)acrylate means at least one of acrylate and methacrylate. In addition, a polyalkylene carbonate such as polyethylene carbonate or polypropylene carbonate dissolved in a solvent such as triethyl acetyl citrate, propylene glycol diacetate, diethyl succinate, ethyl carbitol acetate, triacetin, texanol, dimethyl adipate, ethyl benzoate, or a mixture of propylene glycol monophenyl ether and triethylene glycol dimethyl ether can be used as the organic vehicle.

[0054] The ratio of the resin and the solvent in the organic vehicle is not particularly limited, but is selected so that the viscosity of the organic vehicle can adjust the viscosity of the glass paste. Specifically, the ratio of the resin and the solvent in the organic vehicle is preferably about 3:97 to 30:70 in terms of the mass ratio of the resin:solvent.

[0055] The ratio of the mixed material and the organic vehicle in the glass paste is appropriately adjusted according to the desired viscosity of the glass paste. Specifically, the mass ratio of the mixed material to the organic vehicle is preferably about 65:35 to 90:10. In addition to the mixed material and the organic vehicle, the glass paste may contain known additives as necessary and within the limits of the present invention.

[0056] The glass paste is prepared by a known method using a rotary mixer equipped with stirring blades, a roll mill, a ball mill, or the like.

[0057] The glass paste or sealing material of the present invention is preferably used for sealing glass substrates. The glass substrates can be sealed by a known method, for example, the following procedure. When two glass substrates are sealed together, a layer of glass paste or sealing material is first formed on a portion of one surface of one of the glass substrates, and the layer thus formed is pre-fired. The pre-fired layer is preferably heated at a temperature 30 to 60° C. higher than the softening point of the glass composition. Next, the pre-baked layer is brought into contact with one side of the other glass substrate, and the pre-baked layer is heated in this state. The method for heating the pre-baked layer is not particularly limited, but since local heating is possible, irradiation with electromagnetic waves is preferred, and irradiation with light is preferred. When light irradiation is performed to heat the pre-baked layer, irradiation with laser light is also preferred. The glass composition of the present invention has the above-mentioned fluidity increase rate, and therefore has excellent fluidity and bubbling resistance when heated according to the above-mentioned procedure.

[0058] <Sealed package> The glass composition of the present invention can be preferably used as a sealed package. For example, in a sealed package having a first substrate, a second substrate disposed opposite the first substrate, and a sealing layer disposed between the first substrate and the second substrate and bonding the first substrate to the second substrate, the sealing layer preferably contains the glass composition of the present invention. An embodiment of the sealed package will now be described with reference to the drawings.

[0059] Fig. 1 is a plan view showing a state in which an electronic element 18 is sealed in a sealed package 10. Fig. 2 is a cross-sectional view taken along line AA in Fig. 1. 1 and 2 includes a first substrate 12, a second substrate 14 disposed opposite the first substrate, and a sealing layer 16 disposed between the first substrate 12 and the second substrate 14 and bonding the first substrate 12 and the second substrate 14. An electronic element 18 is sealed in the sealed package 10, and the electronic element 18 is not in direct contact with the outside air.

[0060] The first substrate 12 and the second substrate 14 are preferably glass substrates. The glass substrate is not particularly limited, but for example, a soda lime glass substrate and an alkali-free glass substrate are used. Examples of soda lime glass substrates include AS and PD200 (both manufactured by AGC, product names), and chemically strengthened versions of these. Examples of alkali-free glass substrates include AN100 (manufactured by AGC, product name), EAGLE2000 (manufactured by Corning, product name), EAGLEGX (manufactured by Corning, product name), JADE (manufactured by Corning, product name), #1737 (manufactured by Corning, product name), OA-10 (manufactured by Nippon Electric Glass Co., Ltd., product name), and Tempax (manufactured by Schott, product name).

[0061] The sealing layer 16 comprises the glass composition of the present invention. The sealing layer 16 may contain components other than the glass composition of the present invention. Examples of the components other than the glass composition of the present invention include components contained in the sealing material and materials contained in the glass paste.

[0062] The electronic element 18 is not particularly limited. For example, an organic electroluminescence element, a plasma light-emitting element, an organic thin-film solar cell element, a liquid crystal element, and a dye-sensitized solar cell element can be mentioned. Each of the above elements may have a known structure. Among them, the electronic element 18 is preferably an organic electroluminescence element.

[0063] The above-mentioned sealed package 10 can be manufactured, for example, by the following procedure: The procedure for producing a structure in which an electronic element 18 is sealed in the sealed package 10 will be described below.

[0064] First, the glass paste of the present invention is applied (not shown) to the area of ​​the second substrate where sealing is to be performed (see the area of ​​the sealing layer 16 in FIG. 1). The applied glass paste is dried to form a coating layer. The application method is not particularly limited, and examples thereof include printing methods such as screen printing and gravure printing, and dispensing methods. Drying is performed to remove the solvent contained in the glass paste. Drying may be performed, for example, at a temperature of 120° C. or higher for 10 minutes or more.

[0065] The glass paste applied to the second substrate on which the coating layer is formed is pre-fired to form a pre-fired layer 16a on one surface of the second substrate 14, as shown in Fig. 3. The pre-fire is preferably performed by heating the coating layer to a temperature equal to or higher than the softening point (Ts) of the glass composition of the present invention contained in the glass paste. The preferred heating temperature is as described above.

[0066] 4, the first substrate 12 and the second substrate 14 are superimposed on each other. First, the first substrate 12 and the electronic element 18 provided on one surface of the first substrate 12 are prepared. Then, the first substrate 12 and the second substrate 14 are superimposed on each other such that the electronic element 18 is disposed between the second substrate 14 and the first substrate 12. At this time, the first substrate 12 and the second substrate 14 are in contact with each other via the provisionally fired layer 16a.

[0067] In the state shown in Fig. 4, the provisionally fired layer 16a is fired to form the sealing layer 16. Fig. 5 shows a state in which the provisionally fired layer 16a is fired by irradiation with laser light (white arrow in Fig. 5) on the left side of the page to form the sealing layer 16. When the provisionally fired layer 16a formed in the state shown in Fig. 5 is fired over its entire periphery, the sealed package 10 shown in Figs. 1 and 2 is obtained.

[0068] The above-mentioned firing can be carried out by a known means, and the method is not particularly limited as long as it can heat the pre-fired layer 16a. For example, the method of heating the pre-fired layer 16a includes irradiation with electromagnetic waves, and examples of the electromagnetic waves include microwaves, infrared rays, visible light, and ultraviolet rays. It is also preferable that the electromagnetic waves (particularly light) to be irradiated are lasers. The type (wavelength) of the laser is not particularly limited, and examples of the laser include laser light such as semiconductor lasers, carbon dioxide lasers, excimer lasers, YAG lasers, and HeNe lasers. When laser irradiation is used as a method for firing the provisionally fired layer 16a, the output of the irradiated laser can be appropriately adjusted depending on the line width, thickness, etc. of the provisionally fired layer 16a. Alternatively, the method for firing the provisionally fired layer 16a may involve heating the first substrate 12, the second substrate 14, the provisionally fired layer 16a, and the electronic element 18 as a whole in a furnace.

[0069] <Organic electroluminescence panel> The organic electroluminescence panel of the present invention comprises a substrate, a laminated structure having an anode, an organic thin film layer, and a cathode, and a glass member, in that order, and a sealing layer that bonds the substrate and the glass member, the sealing layer including the glass composition of the present invention. The organic electroluminescent panel of the present invention corresponds to an embodiment in which, in a structure in which an electronic element 18 is sealed in a sealed package 10 shown in Figures 1 and 2, the electronic element 18 is an organic electroluminescent element including an anode, an organic thin film layer, and a cathode, and the first substrate 12 is a substrate in the above-mentioned laminated structure. The organic electroluminescence panel of the present invention may have a structure that an organic electroluminescence element (an element comprising an anode, an organic thin film layer, and a cathode) in the art may have. The respective preferred aspects are as described above, and therefore description thereof will be omitted. EXAMPLES

[0070] The present invention will be described in further detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples. Examples 1 to 6 are working examples, and Examples 7 to 9 are comparative examples.

[0071] <Production of Glass Composition (Glass Powder)> The raw materials were mixed so as to obtain the composition shown in Table 1 below, placed in a platinum crucible, and heated and melted for 1 hour in an electric furnace at 950 to 1150° C. to obtain molten glass. The composition shown in Table 1 is expressed in mole percent based on oxides. The resulting molten glass was formed into a thin glass sheet. The molded thin glass is crushed in a rotary ball mill, classified through a sieve, and then classified into D 50 The glass powders used in Examples 1 to 9 having a particle size of 0.5 to 15 μm were obtained. The composition of the obtained glass powders was determined by the above-mentioned method, and was found to be consistent with the composition shown in Table 1.

[0072] <Measurement of physical properties> [Differential thermal analysis (DTA)] Differential thermal analysis (DTA) was carried out under the following conditions. The glass composition was thermally analyzed at a heating rate of 10°C / min using a differential thermal analysis (DTA) device TG-DTA8122 manufactured by Rigaku Corporation, to obtain a DTA curve. From the obtained DTA curve, the glass transition point Tg, softening point Ts, crystallization onset temperature Tcs, and crystallization temperature Tcp (each in °C) were obtained. The first inflection point of the DTA curve was determined as the glass transition point Tg, the fourth inflection point as the softening point Ts, the start point of the exothermic peak as the crystallization onset temperature Tcs, and the exothermic peak temperature as the crystallization temperature Tcp. From the DTA curve obtained by performing DTA, the glass transition point (Tg) and the softening point (Ts) were determined by the above-mentioned method. The obtained parameters are shown in Table 2 below.

[0073] [Liquidity Increase Rate] The fluidity increase rate was calculated from the Ts value obtained by the above procedure. The temperature values ​​(T50 and T70) used to calculate the fluidity increase rate are shown in Table 2 below. T50 is a temperature 50°C higher than the value T1 obtained by rounding off the Ts value to the nearest 1, and T70 is a temperature 70°C higher than T1. Furthermore, a cylindrical molded body having a diameter of 15 mm was formed by the above procedure, and the molded body was held at the above T50 and T70 for 10 minutes, and the diameter when held at each temperature was measured. From each of the measured diameters (R50 and R70 above), the fluidity increase rate (unit: % / ° C., fd in formula (1)) was calculated according to formula (1) above. The calculated liquidity increase rate (fd) is shown in Table 1 below.

[0074] <Evaluation> [water resistance] The water resistance was evaluated according to the above procedure and formula (2). The procedure was as described above, and the cylindrical sample was immersed in pure water, and the mass loss rate (ΔW, unit: %) was calculated from the change in mass before and after immersion. The water resistance was evaluated based on the calculated mass loss rate according to the following criteria. The evaluation results of water resistance are shown in Table 1 below. A: Mass loss rate is less than 0.8% ·B: Mass reduction rate is 0.8% or more

[0075] [Foaming resistance] First, a mixed material containing the glass powder of each of the above compositions, a light absorbing substance (laser absorbing substance) and a low expansion filler was mixed with an organic vehicle containing a binder and a solvent to prepare a glass paste. Specifically, first, a glass powder, a light absorbing material, and a low expansion filler were mixed in the following ratios to obtain a mixed material, and then a binder and a solvent were mixed in the following ratios to obtain an organic vehicle.

[0076] (mixed material) Glass powder in each example: 64% by volume Ceramic filler (zirconium phosphate-alumina mixture): 30% by volume Light absorbing material (Fe2O3-CuO-MnO): 6% by volume

[0077] (Organic Vehicle) Binder (ethyl cellulose): 15% by weight Solvent (diethylene glycol mono-2-ethylhexyl ether): 85% by mass

[0078] The obtained mixed material and an organic vehicle were mixed in the following ratio to obtain a glass paste. ·Mixed material: 76% by mass ·Organic vehicle: 24% by mass

[0079] Using the glass paste containing the glass powder of each example obtained, a sealing test was carried out in the following procedure. First, two glass substrates (25 mm square, 0.5 mm thick) made of alkali-free glass (AN100: manufactured by AGC) were prepared. Each glass paste was applied to one surface of one of the glass substrates using a 400-mesh screen on a frame to form a coating layer. The coating layer was then dried at 140°C for 10 minutes, and further heat-treated at 350°C for 20 minutes to remove the binder, followed by pre-firing at 400°C for 10 minutes to form the coating layer into a pre-firing layer (see FIG. 3). The pre-firing layer was adjusted so that it would have a width of about 600 μm and a thickness of 7 to 11 μm when used as a sealing layer in the subsequent processing step. Next, the other glass substrate and the glass substrate on which the pre-fired layer was formed were overlapped to form an assembly. In the assembly, the pre-fired layer was in contact with the surface of the other glass substrate (see FIG. 4). This assembly was irradiated with laser light from the glass substrate side on which the pre-baked layer was formed, and the pre-baked layer was melted and rapidly cooled and solidified to form a sealing layer (see FIG. 5). By the above procedure, a sealed package was obtained. The laser beam used was a semiconductor laser with a wavelength of 940 nm, the spot diameter was 1.6 mm, and the scanning speed was 21 mm / sec. The output of the laser light was set so that the width of the sealing layer became 110% of the width of the provisionally fired layer.

[0080] The sealed package obtained by the above procedure was cut in a direction perpendicular to the line width direction of the frame of the sealing layer, and the cross section of the sealing layer was observed with a scanning electron microscope (SU3500, manufactured by Hitachi High-Technologies Corporation). The cross section of the sealing layer was observed to check for the presence or absence of voids (air bubbles), and the foaming resistance was evaluated according to the size of the voids according to the following criteria. A: No voids larger than 1 / 4 of the thickness of the sealing layer are observed in the cross section of the sealing layer. ·B: No voids exceeding 80% of the thickness of the sealing layer are observed in the cross section of the sealing layer, but voids measuring 1 / 4 to 80% of the thickness of the sealing layer are observed. C: Voids exceeding 80% of the thickness of the sealing layer are observed in the cross section of the sealing layer. In addition, if large voids occur in the sealing layer, it can cause poor bonding. From a practical standpoint, an A rating is preferable.

[0081] <Result> The physical properties of each of the above glass powders (glass compositions), the evaluation results of the water resistance of the glass compositions, and the evaluation results of the foaming resistance of glass pastes using each of the glass powders are shown in Table 1 below. In the table, Tg and Ts represent the glass transition point and the softening point, respectively. In the table, T50, T70, R50 and R70 are as defined above.

[0082] [Table 1]

[0083] From the results shown in Table 1, it was confirmed that when the value of the fluidity increase rate (fd) is 1.10% / °C or more, the foaming resistance is excellent. [Explanation of symbols]

[0084] 10 Sealed Package 12 First substrate 14 Second board 16 Sealing layer 16a Pre-fired layer 18 Electronic elements

Claims

1. A glass composition that is substantially alkali metal and lead free, comprising: A glass composition having a fluidity increase rate per degree Celsius of 1.10% / °C or more in a temperature range from 50°C higher than the softening point of the glass composition to 70°C higher than the softening point of the glass composition.

2. The glass composition according to claim 1 , comprising at least vanadium and tellurium.

3. In mole percent based on oxide, V 2 O 5 25.0 to 50.0%, TeO 2 and ZnO in an amount of 5.0 to 30.0%, V 2 O 5 and TeO 2 3. The glass composition according to claim 2, wherein the total content of Cd and ZnO is 84.0 to 92.0%.

4. In mole percent based on oxide, A 2 O 3 , La 2 O 3 , Y 2 O 3 and CuO in an amount of 0.1 to 5.0%; V 2 O 5 and TeO 2 The glass composition according to claim 2 or 3, wherein the total content of is 63.0 to 70.0%.

5. Further, the composition contains one or more components selected from the group consisting of phosphorus and copper, In mole percent based on oxide, TeO 2 Contains 42.0 to 52.0% V 2 O 5 and TeO 2 The glass composition according to claim 2 or 3, wherein the total content of is 70.0 to 85.0%.

6. In mole percent based on oxide, La 2 O 3 , and Y 2 O 3 Contains 0.1 to 5.0% of one or more selected from the group consisting of 4. The glass composition according to claim 1, wherein the BaO content is 0.1 to 4.5%.

7. In terms of oxide mole percent, Nb 2 O 5 The glass composition according to any one of claims 1 to 3, wherein the content of is 2.0 to 10.0%.

8. 4. A glass powder comprising the glass composition according to claim 1, wherein the volume-based 50% particle size in a cumulative particle size distribution is 0.1 to 100 μm.

9. A sealing material comprising the glass powder according to claim 8 and at least one of a low expansion filler and an electromagnetic wave absorbing substance.

10. A glass paste comprising the glass powder according to claim 8 and an organic vehicle.

11. The glass paste of claim 10 further comprising at least one of a low expansion filler and a laser absorbing material.

12. A first substrate; a second substrate disposed opposite the first substrate; a sealing layer disposed between the first substrate and the second substrate and bonding the first substrate and the second substrate together, A sealed package, wherein the sealing layer comprises the glass composition according to any one of claims 1 to 3.

13. The device includes a substrate, a laminated structure having an anode, an organic thin film layer, and a cathode, and a glass member in this order; a sealing layer that bonds the substrate and the glass member; An organic electroluminescent panel, wherein the sealing layer comprises the glass composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Glass composition, glass powder, sealing material, glass paste, sealing method, sealing package and organic electroluminescence element

    JP2021066647A